2005
DOI: 10.1055/s-2005-837574
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Neonatal MRI with Respect to Late MRI Findings and Clinical Outcome. A Study in Infants with Periventricular Densities on Neonatal Ultrasound

Abstract: Neonatal MRI is able to predict the precise localization and size of perinatal leukomalacia on follow-up MRI and provides a good prediction of neurological outcome at 1 1/2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…28 Others have revealed that MRI may provide additive information to predict neuromotor outcomes, 29 complementary to specific findings such as periventricular echodensities by CUS, 30 or neurologic examination. 31,32 Our results suggest that some type of near-term imaging (late CUS or brain MRI) adds value over perinatal/neonatal factors and early CUS alone.…”
Section: Discussionmentioning
confidence: 99%
“…28 Others have revealed that MRI may provide additive information to predict neuromotor outcomes, 29 complementary to specific findings such as periventricular echodensities by CUS, 30 or neurologic examination. 31,32 Our results suggest that some type of near-term imaging (late CUS or brain MRI) adds value over perinatal/neonatal factors and early CUS alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the aetiology of CP in individual cases is often difficult to precisely establish [Paneth et al, 2006], and the variability in the cerebral injury covered by the term CP means that outcomes predicted by current diagnosis can be inconsistent [Bartlett and Palisano, 2002]. Multiple semi-quantitative scoring systems have been developed to address these issues and to standardise the assessment of MRIs [Cioni et al, 1997;Fiori et al, 2014;Inder et al, 2003;Kidokoro et al, 2013;Miller et al, 2005;Shiran et al, 2014;Sie et al, 2005;Skiöld et al, 2013]. In these methods, specific criteria of brain injury are graded based on their severity, or anatomical regions are given a discrete score based on whether the region contained injury or was healthy, and then summed to provide a total measure of injury.…”
Section: Imaging Of Brain Injurymentioning
confidence: 99%
“…In these methods, specific criteria of brain injury are graded based on their severity [Inder et al, 2003;Kidokoro et al, 2013;Miller et al, 2005;Shiran et al, 2014;Sie et al, 2005;Skiöld et al, 2013], or anatomical regions are given a discrete score based on whether the region contained injury or was healthy Shiran et al, 2014]. The sum of these individual sub-scores of injury provides a total measure of injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations